THE ROLE OF PERCEIVED QUALITY AS AN INTERVERNING VARIABLE OF PERCEIVED PRODUCT INNOVATION ON PURCHASEINTENTION ON SCARLETT PERFUME PRODUCTS - Amin, Ahmad Fajrul; Vania, Amelindha (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The retail industry is seeing intensified competition as economic growth and corporate development continue to advance. Scarlett is a retail product that consistently introduces innovations periodically. Scarlett introduced her latest creation, specifically a fragrance. The objective of this study is to ascertain the impact of perceived product innovation, as assessed through quality, on consumers' inclinations to purchase Scarlett perfume items. This study is a quantitative research conducted with a descriptive methodology on a sample of 198 students from State University in Madura. The research employed online sampling through the distribution of questionnaires using Google Form, and the obtained data was analysed using the statistical programme Sm|art-PLS 4.0. The research findings indicate that the perception of product innovation has a notable impact on the perception of quality. Additionally, the perception of quality has a significant influence on the intention to purchase. Furthermore, the perception of product innovation also has a significant effect on the intention to purchase. Moreover, the perception of quality acts as a mediator and positively influences the relationship between the perception of product innovation and the intention to purchase Scarlett perfume.